Capturing the Extreme in Volcanology: The Case for the Term “Supervolcano” - de Silva, Shanaka; Self, Stephen (Frontiers in Earth Science, 2022)
Although evocative, the term supervolcano has a checkered history of hyperbole and misuse to the point that it seems unprofessional. However, “supervolcano” is firmly embedded in volcanological discourse and we make the case that it is useful if defined and used correctly. To this end we examine the etymology of supervolcano and demonstrate its’ dependence on the term supereruption. We build on the work of colleagues to propose that supervolcano be restricted to a volcano that has been the site of at least one silicic explosive eruption of Magnitude of 8 (M 8) or greater. Based on this, nine active supervolcanoes are found on the Earth today and although all are calderas, we contend that referring to them simply as large calderas or caldera complexes obviates clear magmatic, volcanological, and structural extremes that distinguish supervolcanoes from other caldera complexes. Such supervolcanoes may produce eruptions that exceed M 9 but we stress that most eruptions from supervolcanoes are actually small effusive eruptions. Basaltic explosive supereruptions remain enigmatic on Earth and therefore we advise against the use of supervolcano for any basaltic volcano or province on Earth.